An Increased on Firm Value: Insight in State Owned Enterprises that Listed on the Indonesia Stock Exchange 2013-2018 - Khaq, Akhsanul; Syahrial, Dermawan; Susilo, Wilhelmus Hary (International Journal of Economics and Financial Issues, 2020)
In an emerging market, the firm value has become an important variable for raise capital and sustainable- performance within the national economic development that conducted within Indonesian as the most economically- charged. The purpose of this study is to examine an effects of corporate governace perceptions ındex (CGPI), debt to equity ratio (DER), size of firm, and exchange rate, on state owned enterprises (SOEs) financial performance, and their implication on SOEs values that listed on the Indonesia Stock Exchange in 2013- 2018. Furthermore, the quantitative approach conducted within inquiry this research that used Eviews ver. 9.0 for analysis the panel data. Hence, the SOEs that listed on the Indonesia Stock Exchange in 2013-2018 as the populations. This study found that CGPI, DER, and exchange rate have significant affected on SOEs Financial Performance that listed in Indonesia Stock Exchange and the simultaneously contributions with R-square of 0.975 and except firm size that is not significant. Finally, the results also indicate firms may have to these variables and financial performance was a significant impact on SOEs values, within the R-square of 0.874, even if SOEs are not doing business in our country and sustainability business. Keywords: State Owned Enterprises, Firm Value, Financial Performance, Corporate Governace Perceptions Index, Debt to Equity Ratio, Firm Size, Exchange Rate JEL Classifications: G3, L25 DOI: https://doi.org/10.32479/ijefi.9219